Factors Affecting Students Choice of Higher Education Institution: A Malaysian Perspective - Moorthy, Krishna; Johanthan, Sonia; Hung, Chin Chee; Han, Khaw Chee; Zheng, Ng Zi; Cheng, Wong Yau; Yuan, Woon Huai (World Journal of Vocational Education and Training, 2019)
Malaysia is currently having an increased competition among higher education institutions. The ambition of this research is to identify the relationship between the marketing mix model (7P) and students’ choice of Private Higher Education Institutions (PHEIs) in Malaysia. Primary data have been obtained from students in selected higher education institutions in Malaysia. The target respondents have been selected by using quota sampling method under the non-probability sampling technique. Self-administered questionnaires were distributed to the target respondents from different PHEIs (UniKL, UTAR, TARUC and SEGi University) and 302 useful questionnaires were collected. All questions are measured using a 5-point Likert Scale. The result reveals that the marketing mix (product, place, price, promotion, people, process and physical evidence) has a significant influence on students’ choice of PHEI. This research provides a better insight to help PHEIs to understand and develop best services to increase the students’ enrolment. This research also demonstrates the importance of the marketing mix (7p) model in higher education institutions’ perspective.